Development and Characterization of Advanced Nano-Coating with CeO₂, Al₂O₃, ZnO, and TiO₂ Nanoparticles for Enhanced Durability and Corrosion Resistance (International Journal of Scientific Research and Management (IJSRM), 2024)
This study introduces an innovative sol-gel nano-coating designed to address silica scaling and corrosion in hydrothermal and high-stimulation environments. By incorporating CeO₂, Al₂O₃, ZnO, and TiO₂ nanoparticles into a polymer matrix through precise sonication techniques, the coating achieves uniform dispersion and enhanced functional performance. The meticulous characterization of nanoparticle integration optimizes mechanical strength, thermal stability, and chemical resistance. Applied via a directional supplying device, the nano-coating is mechanically deposited onto the cemented walls of wells, providing robust protection against scaling and corrosion across diverse conditions, including varying temperatures and pH levels. Laboratory testing demonstrates significant reductions in silica scaling and corrosion rates, confirming the coating’s efficacy in maintaining production efficiency in both hydrothermal projects and fracking operations. This paper details the synthesis process and molecular chemistry involved in nanoparticle integration, alongside the resultant structural properties of the coating. Thermogravimetric analysis (TGA) assesses thermal stability, while kinetic models such as Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunose (KAS) evaluate activation energy without assuming specific reaction models. The findings highlight the potential of this advanced nano-coating as a robust solution for enhancing operational longevity and efficiency in challenging industrial applications.